Coffee intake and the incident risk of cognitive disorders: A dose–response meta-analysis of nine prospective cohort studies. Issue 3 (June 2017) - Wu, Lei; Sun, Dali; He, Yao
Summary: Background & aims: Previous epidemiological studies have provided inconsistent conclusions on the impact of coffee consumption in the developing of cognitive disorders. However, no previous meta-analysis has pooled the evidence from the prospective cohort studies to assess the influence of coffee drinking and its potential dose–response patterns on the risk of developing cognitive disorders specifically. Methods: Two databases (PubMed and Embase) were searched for evidence of cohort studies from inception to February 2016. We used a generic inverse-variance method with a random-effects model to pool the fully adjusted relative risks (RRs) and the corresponding 95% confidence intervals (CIs). In the dose–response analyses, a generalized least-squares trend estimation model was applied to computing the study-specific slopes. Results: Nine prospective cohort studies involving 34, 282 participants were included in our study. The duration of follow-up years ranged from 1.3 to 28. Compared with <1 cup, daily drinking of 1–2 cups of coffee was inversely linked with the occurrence of cognitive disorders (i.e., Alzheimer's disease, dementia, cognitive decline, and cognitive impairment), and the pooled RR (95% CI) was 0.82 (0.71, 0.94) with evidence of non-significant heterogeneity (I 2 = 25%). Non-significant differences were presented for the association between coffee consumption (>3 vs. <1 cup/d) and incident cognitive disorders. The dose–response analysis showed a "J-shaped" curve relationship of the risk of developing cognitive disorders with coffee consumption. Conclusions: A "J-shaped" association was presented between coffee intake and incident cognitive disorders, with the lowest risk of incident cognitive disorders at a daily consumption level of 1–2 cups of coffee.